Características agronômicas e microbiológicas da couve manteiga (Brassica Oleracea L.) irrigada com água residuária tratada em ambiente protegido - Ramos, Francyelle Souza de Menezes (2021)
The use of treated wastewater for irrigation can become an alternative for regions that face water scarcity, with this the reuse of wastewater in irrigation has been practiced. The reuse of the natural resource, water, is increasingly taking place in the scientific community. Thus, the work aimed to evaluate the viability of reusing effluents from a sewage concentration system by stabilization ponds in the irrigation of kale, using agronomic and microbiological characteristics of the crop. The research was carried out in a protected environment, located at the Federal University of Sergipe. The irrigation depths were obtained as a function of the crop evapotranspiration (ETc). The experimental design was in blocks composed of fifteen treatments, with three types of water T1 (100% water from the supplying utility), T2 (50% water from the supplying utility + 50% effluent), T3 (100% effluent), five irrigation depths L1 (50% of ETc), L2 (75% of ETc), L3 (100% of ETc), L4 (125% of ETc), L5 (150% of ETc) and three replicates, totaling 45 pots. The agronomic variables evaluated were number of leaves, leaf length, fresh weight and root length. The microbiological analyzes analyzed were Salmonella and thermotolerant coliforms (coliforms at 45ºC). It is concluded from this work that the use of treated wastewater in the irrigation of the culture of Couve Manteiga did influence the agronomic characteristics evaluated with a significance level of 5%. In the microbiological analyzes, verifying the results of the analysis of coliforms at 45°C and Salmonella, carried out at ITPS and comparing with the maximum levels admitted by Anvisa Resolution 12/2001 for the culture of Kale Butter, it is concluded that the values determined in the laboratory they are lower than the parameters established by ANVISA (National Health Surveillance Agency), so it is feasible to use wastewater to irrigate the cabbage crop, without compromising human consumption. For studies other than the irrigation depth, the inflection point was obtained by applying 196% of ETc, with a fresh mass of 107 grams. For supply water the maximum peak of fresh mass was obtained by applying 123% of ETc, with 74.21 grams. Therefore, with the nutritional input that the effluent has and in greater quantity, it obtained better results.